Towards high-resolution laser ionization spectroscopy of the heaviest elements in supersonic gas jet expansion - R. Ferrer (Nature Portfolio, 2017)
It is challenging to explore properties of heavy elements as they can only be produced artificially. Here, the authors demonstrate a high resolution spectroscopy method, studying the properties of actinium, which can be extended to the study of other elements located at the end of the periodic table.